Locomotor characteristics of intense accelerations according to the playing position in top Spanish football teams during competition - González-Rodenas, Joaquín; Moreno-Pérez, Víctor; Castaño-Zambudio, Adrián; López-Del Campo, Roberto; Nevado, Fabio; Coso, Juan (Biology of Sport, 2025)
This study aimed to characterise the locomotor characteristics of intense relative accelerations (> 50% of maximal acceleration-speed profile) according to playing positions in top-ranked Spanish football teams. A total of 271,535 accelerations performed by 102 football players of the top four teams during the 2023–2024 LaLiga season were registered by a multiple-camera computerised tracking system (TRACAB; ChyronHego, USA). A generalized linear mixed model compared the acceleration characteristics (number, distance, duration, intensity and speed) across playing positions (central defender: CD, full back: FB, central midfielder: CM, attacking midfielder: AM, winger: W and forward: FW) considering the effect of contextual variables. CD exhibited less intense accelerations per minute than the rest of the playing positions ( p < 0.05). W exhibited the greatest distance per acceleration (estimated mean (EM) = 9.08 m), longest duration (EM = 2.18 s), highest peak speed (EM = 19.5 km·h −1 ), and highest speed at maximum acceleration (EM = 12.8 km·h −1 ) ( p < 0.05). FW exhibited the highest peak acceleration per action (EM = 3.14 m·s −2 ) and average acceleration per action (EM = 1.76 m·s −2 ) ( p < 0.05). AM and CM registered higher initial speed ( p < 0.05) and exhibited the lowest values for peak acceleration per action ( p < 0.05), compared to the other playing positions. In contrast, CD and CM showed the shortest distances and slowest speeds ( p < 0.05). In conclusion, W and FW exhibited higher acceleration intensity than the rest of the playing positions, while CD and CM obtained the lowest values for distance, duration, and speed.